A taxonomy of the relevant actors in the European energy transition - Till Fladung; Julia Hoffmann; Mathias Mier; Mustafa Ispa (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2025)
The European energy market is comprised of a diverse range of actors, each with distinct roles and objectives. This paper proposes a taxonomy that categorizes these actors into five groups: governance, grid and transport, supply, demand, and investors. Utilizing extant literature, we identify salient characteristics and distinctions within these groups through analyzing their interconnections and interactions. By systematically mapping energy flows and investment patterns, we present a structured overview of the market's evolving landscape and its implications for the energy transition, particularly concerning the debate on the necessity of capacity mechanisms.
Keywords: Q40; L20; D22; 016; D24; 330; Energy transition; Actor Heterogeneity; Firm Behavior; Finance; Capacity mechanisms